A Study of Front Office Staff’s Perception on Importance of English in Tegal City - Hana Fithriyani; Puput Anggraeni (Chatra: Jurnal Pendidikan dan Pengajaran, 2025)
Purpose – The aim of this research is to determine the perception of front office staff regarding the importance of English in Tegal City.  Design/methods/approach – The research object was front office staffs of a 3-star hotel in Tegal City.  The design of this research is a case study with data collection methods in the form of questionnaires, observation and literature study.  Data were analyzed using descriptive statistical analysis with a quantitative approach.Findings - The results of the research showed that front office staff's perception of the importance of English in Tegal City is viewed positively. English language skills are one of the important things that FO staff must master. The factors underlying this are the large number of FO terms that use English, the requirement to be able to communicate in English with foreign guests, as well as the obligation to provide maximum professional and friendly service. Respondents' interest in maximizing potential in English skills is seen as a good perception of the importance of English. Research implications/limitations – This study focuses on front office staff working at three-star hotels in Tegal City. A total of eight respondents participated in the research, all of whom are employed in the front office departments of these hotels. The main objective of this study is to explore their perceptions regarding the importance of English language skills in the hospitality industry, particularly in delivering quality service to guests.